An Effort to Improve Student Learning Outcomes in Civics through the Application of the ALTRRQ in Fifth Grade Students of Negeri Wakarleli Elementary School - Maudara, Nandito; Kempa, Titin (Universitas Pattimura, 2025)
This study aims to describe the improvement of Civics (PKn) learning outcomes through the implementation of the Active Learning model of the Role Reversal Question (ALTRRQ) type in fifth-grade students at Negeri Wakarleli Elementary School. The data collection methods used in this study included tests, observations, and documentation. The research instruments consisted of test items and observation sheets. The data analysis techniques employed were descriptive quantitative and qualitative analysis. This study was a classroom action research (CAR), consisting of four stages: planning, implementation, observation, and reflection. The subjects of the study were nine fifth-grade students at Negeri Wakarleli Elementary School. The research instruments included teacher activity sheets, student activity sheets, and test questions. The collected data were analyzed using percentage formulas. The results showed that the percentage of teacher activity increased from 72.61% in Cycle I to 97.82% in Cycle II. Student activity also improved, rising from 66.66% in Cycle I to 95.65% in Cycle II. Student learning outcomes increased from 68.97% in Cycle I to 87.17% in Cycle II. Therefore, it can be concluded that the application of the Active Learning model of the Role Reversal Question (ALTRRQ) type in Civics instruction can improve the learning outcomes of fifth-grade students at Negeri Wakarleli Elementary School.